Family Relations, Stress, and Vulnerability: Biobehavioral Implications for Prevention and Practice. Issue 1 (February 2016) - Ha, Thao; Granger, Douglas A.
Abstract: Developmental psychobiology research supports the hypothesis that individual differences in biological stress systems that are sensitive to environmental experiences are associated with individual adjustment problems. Negative social experiences, especially in family contexts, contribute to the dysregulation of set‐points and thresholds of biological stress reactivity that affects long‐term adaptation and adjustment. The goal of this review is to discuss the current findings on how negative parent–child relationships affect the biological stress system. The authors also highlight the importance of family‐based prevention and intervention to decouple links between the psychobiology of the stress response and adjustment problems. They discuss how including indicators of the biological stress system, such as cortisol and salivary alpha amylase, can be useful for family practitioners and researchers.